The Effect of Acupressure Pericardium 6 (P6) Point on Emesis Gravidarum in First Trimester Pregnant Women in the Working Area of Andalas Health Center in 2023 - Alya, Fuja; Sari, Fatmi Nirmala; Intani, Trya Mia (STIKes Alifah Padang, 2023)
Pregnancies with emesis gravidarum reach 12.5% of all pregnancies in the world. In Indonesia, it was found that pregnant women with emesis gravidarum reached 14.8% of all pregnancies. Nearly 60-80% of pregnant women experience nausea in the first trimester. This complaint is a physiological matter, but if it is not immediately resolved it will become a pathological matter. So that there is a need for early management of emesis gravidarum, one of which is non-pharmacological treatment, namely pericardial acupressure. gravidarum in first trimester pregnant women in the working area of Andalas Health Center in 2023. Quantitative research method with a pre-experimental research design with a one group pretest-posttest design approach. Total population of 185 pregnant women with emesis gravidarum and a sample of 36 people, using cluster random sampling technique. This research was conducted in march-august in the working area of the puskesmas in 2023. Data was collected through a 24-hour puqe questionnaire by means of interviews and observations. Data were analyzed univariately and bivariately using the dependent t-test. Based on the results of the study, it was found that the average emesis gravidarum before being given pericardium 6 acupressure was 8.25 while the average nausea and vomiting after being given pericardium 6 acupressure was 5.72. This means that there is an effect of giving pericardium 6 point acupressure on emesis gravidarum in pregnant women in the first trimester. in the Andalas Health Center Work Area in 2023 with a p-value = 0.000. Pericardium 6 acupressure can be applied in midwifery services as a non-pharmacological therapy useful for stimulating the regulatory system and activating endocrine and neurological mechanisms, so as to reduce the frequency of emesis gravidarum in pregnancy.